2013
DOI: 10.1139/apnm-2012-0333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine and carbohydrate mouth rinses on repeated sprint performance

Abstract: Our purpose was to examine the effectiveness of carbohydrate and caffeine mouth rinses in enhancing repeated sprint ability. Previously, studies have shown that a carbohydrate mouth rinse (without ingestion) has beneficial effects on endurance performance that are related to changes in brain activity. Caffeine ingestion has also demonstrated positive effects on sprint performance. However, the effects of carbohydrate or caffeine mouth rinses on intermittent sprints have not been examined previously. Twelve mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
121
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(147 citation statements)
references
References 34 publications
19
121
6
1
Order By: Relevance
“…To this end, Phillips et al (2014) showed that following a series of 5-second CHO mouth rinses, peak power output increased 2.3% from 13.20 ± 2.14Wkg -1 to 13.51 ± 2.19Wkg -1 . Beaven et al (2013) found similar improvements in sprint performance following just one, 5sec CHO mouth rinse. Peak power increased 22.1 ± 19.5W compared with the sprint following a placebo rinse.…”
Section: Cho Mouth Rinsesmentioning
confidence: 63%
“…To this end, Phillips et al (2014) showed that following a series of 5-second CHO mouth rinses, peak power output increased 2.3% from 13.20 ± 2.14Wkg -1 to 13.51 ± 2.19Wkg -1 . Beaven et al (2013) found similar improvements in sprint performance following just one, 5sec CHO mouth rinse. Peak power increased 22.1 ± 19.5W compared with the sprint following a placebo rinse.…”
Section: Cho Mouth Rinsesmentioning
confidence: 63%
“…Other ergogenic effects are likely dependent upon the exercise mode undertaken [2][3][4][5] and active ingredients within the swill, e.g., Caffeine [2,6], Carbohydrate [7,8] or Menthol [3]. These ingredients may also be combined with other ergogenic strategies to maximise the influence upon physiological and psychological determinants of fatigue [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Different methodological factors have been shown to influence the effect that CHO mouth rinse has on performance, such as the duration of the solution being in the mouth (Pottier et al, 2010;Sinclair et al, 2014), nutritional status (Beelen et al, 2009;Carter et al, 2004;Fares and Kayser, 2011;Lane et al, 2013) and the type of exercise being undertaken (Beaven et al, 2013;Bortolotti et al, 2013;Chong et al, 2011;Dorling and Earnest, 2013). Not all studies using CHO mouth rinse have reported significant improvements in performance (Beelen et al, 2009), however the majority of these studies did observe improvements in performance just not with statistical significance.…”
Section: Introductionmentioning
confidence: 99%